Hydrogenation of cyclohexene catalyzed by nanoporous SPE-PtNi/C membrane electrode. (12th January 2022) - Yang, Bin; Fang, Liudang; Zan, Linhan; Cai, Jiaxian; Feng, Yunhao; Li, Xudong
Abstract: Implementing large-scale synthesis of nanoporous PtNi/C catalysts for hydrogenation processes of unsaturated organic compounds under atmospheric pressure at temperatures below 100 °C is an urgent task. In this paper, a nanoporous SPE-PtNi/C membrane electrode is prepared by ion beam sputtering, ultrasonic-assisted electrochemical dealloying, and hotpressing. Special attention is paid to the analysis of the electrochemical properties, phase structure, surface morphology, active constituent distribution, and catalytic efficiency for cyclohexene hydrogenation of the produced electrode in comparison with those of commercial Pt/C catalysts. The results show that the ultrasonic-assisted electrochemical etching temperature exerts the most significant effect on the catalytic activity of the catalyst under consideration. In particular, the treatment of PtNi/C in 0.7 mol/L HClO4 for 1.5 h at the optimized temperature of 50 °C enables one to increase the catalytic activity by 25.20% at decreasing the Pt-loading content by 88.85% compared with commercial Pt/C. Furthermore, the nanoporous structure of the PtNi/C surface allows the binding energy of Pt 4f7/2 to be reduced by 0.23 eV due to the Ni loss and the crystal plane shrinkage from NiPt, which enhances the compressive strain of the lattice structure of exposed Pt and increases the number of active sites. Finally, the use of a nanoporous SPE-PtNi/C membrane electrode could increase the yield of cyclohexene during the hydrogenation reaction by 179% at simultaneously improving the current efficiency by 69%. Graphical abstract: The nanoporous SPE-PtNi/C film electrode prepared by ion beam sputtering and ultrasound-assisted electrochemical de-alloying has low Pt loading, high specific surface area, in addition to good low-temperature catalytic hydrogenation activity, and has promising applications in hydrogen storage. Image 1 Highlights: Preparation of Pt-based nanocrystalline catalysts by ion beam sputtering. Nanoporous catalysts prepared by ultrasound-assisted electrochemical dealloying. The nanoporous PtNi/C membrane electrode has good catalytic activity.